(untitled) (International Journal of Ayurveda and Pharma Research, 2021)
Introduction: Siravedhana, is an important para surgical procedure to withdraw the vitiated blood from body but before performing it the knowledge of Avedhya Sira is mandatory as any injury to these can cause disability or even death. There is total 98 Avedhya Sira in the body. Out of which two are pertaining to the region of Hanu. Any injury to these can cause similar consequences. But the exact location and the structural entity pertaining to it is not clearly mentioned in the classic texts. Material and Methods: Conceptual study carried out by reviewing classical texts, contemporary science, journals, published research works. Conclusion: On the lateral aspect of the head near the anterior margin of the auricle in front of the tragus, the Maxillary artery and Pterygoid venous plexus can be considered as Hanugata Avedhya Sira based on their location and Viddha Lakshana.